2021
DOI: 10.3390/rs13142668
|View full text |Cite
|
Sign up to set email alerts
|

Lidar-Based Morphometry of Conical Hills in Temperate Karst Areas in Slovenia

Abstract: Conical hills, or residual hills, are frequently mentioned landforms in the context of humid tropical karsts as they are dominant surface elements there. Residual hills are also present in temperate karsts, but generally in a less remarkable way. These landforms have not been thoroughly addressed in the literature to date, therefore the present article is the first attempt to morphometrically characterize temperate zone residual karst hills. We use the methods already developed for doline morphometry, and we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
3
0
2
Order By: Relevance
“…However, when a tiny depression is found within a larger depression, then it is more realistic to delineate the larger depression as a doline. Finally, we note that complex (nested) depressions can be technically characterized by the "sinkhole rank" (see [15,97] for details).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when a tiny depression is found within a larger depression, then it is more realistic to delineate the larger depression as a doline. Finally, we note that complex (nested) depressions can be technically characterized by the "sinkhole rank" (see [15,97] for details).…”
Section: Methodsmentioning
confidence: 99%
“…In our analysis, in the case of topographic maps, we delineated the dolines using the OCC method, while in the case of LiDAR-based DTMs, dolines were defined by the level of the lowermost point of the doline rim. The details of the delineation algorithm are presented in previous articles [12,15,18,97], so only the major steps and the flowchart (Figure 3) of the algorithm are presented here without further details. Closed depressions, as mentioned above, are often "nested".…”
Section: Methodsmentioning
confidence: 99%
“…Dolin morfometrisi çalışmalarında büyük oranda 1/25.000 ölçekli topoğrafya haritaları kullanılmaktadır (Day, 1983;Denizman, 2003;Öztürk 2018a). Ancak uzaktan algılama alanında yaşanan gelişmelerin bir sonucu olarak farklı çözünürlükte sayısal yükseklik modellerinin (SYM) üretilmeye başlanmasıyla birlikte bu yüksek çözünürlüklü SYM verileri üzerinden otomatik ya da yarı otomatik çıkarım tekniklerine göre dolinleri çizilmeye ve bunlara göre morfometrik özellikler belirlenmeye başlanmıştır (Chen vd., 2018;Telbisz 2021)or residual hills, are frequently mentioned landforms in the context of humid tropical karsts as they are dominant surface elements there. Residual hills are also present in temperate karsts, but generally in a less remarkable way.…”
Section: Veri̇ Ve Yöntemunclassified
“…Çözünürlüğü 1 ile 90 metre arasında değişen LİDAR, ASTER, ALOS, PALSAR, SRTM gibi küresel verilerden otomatik ya da çıkarım tekniklerine göre çok sayıda dolin morfometrisi çalışması yapılmıştır (Siart vd., 2009;Jeanpert vd. 2016;Jones vd., 2018;Theilen-Willige, 2018;Zumpano vd., 2019;Qiu vd., 2020;Telbisz, 2021)this paper examines the application and quality of digital elevation models (SRTM and ASTER DEMs. Küresel ya da ulusal ölçekte ulaşılabilinen bu verilerin yanı sıra insansız hava araçlarından üretilen sayısal yükseklik modellerinden de otomatik çıkarım yöntemi ile dolinler belirlenmeye başlanmıştır (Utlu ve Öztürk 2023).…”
Section: Veri̇ Ve Yöntemunclassified
“…The detection of karst morphologies from DEMs processing is a well-known methodology, largely applied for geomorphological studies, risk and geohazard assessment, and land use management [4][5][6][7][8][9][10]. Studies based on the comparison between DEM and fieldbased data have demonstrated that the use of digital images with an appropriate spatial resolution generally provides reliable results in the morphometric characterization of sinkholes [11,12].…”
Section: Introductionmentioning
confidence: 99%